SECURITY IMPLICATIONS OF THE CONSTITUTIONAL CRISIS IN BOSNIA AND HERZEGOVINA: BETWEEN THE DAYTON CONSTITUTIONAL FRAMEWORK AND INTERNATIONAL INTERVENTIONISM - Lalić, Velibor (Serbian political thought, 2026)
The constitutional crisis in Bosnia and Herzegovina (BiH) represents a complex case of legal and political destabilization in a post-conflict context. This paper analyzes the security implications of the constitutional crisis through the lens of internal political conflicts and international interventionism. It also highlights how the actions of international actors – particularly the Office of the High Representative (OHR) – function as a mechanism for altering the political balance established by the Dayton Peace Agreement. This dynamic generates new sources of instability which, although not yet amounting to a full-scale security crisis, nevertheless produce significant security consequences. The liberal project of state-building and the policy of international interventionism, rather than fostering reconciliation, have led to growing ethnic polarization and the weakening of institutional functionality. The paper points out a research gap in the existing literature, which has neglected systematic consideration of the security aspects of international interventionism on domestic developments in BiH, and argues that a return to the constitutional principles of the Dayton Peace Agreement may provide a framework for overcoming the current challenges.